The Implementation of Hazard Analysis and Critical Control Point (HACCP) in The Frozen Chicken Meat Distribution Chain in Sikka Regency - Dua Bura, Maria Antonia Yersi; Effendi, Mustofa Helmi; Puspitasari, Yulianna; Rahardjo, Dadik; Tyasningsih, Wiwiek; Rachmawati, Kadek (Fakultas Kedokteran Hewan Universitas Wijaya Kusuma Surabaya, 2024)
Food safety has become a global issue. Hazard analysis and critical control points (HACCP) is a food safety assurance system in the world that emphasizes prevention efforts. This research is a qualitative descriptive epidemiological study which aims to examine the application of HACCP in the distribution chain of frozen chicken meat in Sikka Regency on the growth parameters of total bacteria, Salmonella, and antibiotic residues through field observations at supplier companies and retailers, as well as laboratory tests on 30 frozen chicken meat samples, and 30 fresh chicken meat samples as a comparison. Laboratory tests found antibiotic residues in 60% of samples (16.7% in fresh chicken meat), and microbial contamination in 33% of samples without Salmonella contamination (40% in fresh chicken meat without Salmonella contamination). Monitoring of antibiotic residues has not been carried out properly by supplier companies because the number of samples is very small, sales in markets without refrigeration facilities for up to five hours together with fresh chicken or near fresh fish allows contamination of chicken meat. HACCP principles have not been properly applied in the frozen chicken meat distribution chain. Guidance and regular monitoring are needed so that the quality of frozen chicken meat is maintained.